Potencialização da compostagem com aplicação do biocomposto e dimensionamento de pátio para cidade de médio porte - JERÔNIMO, Guilherme Junqueira (2019)
The production of solid waste in contemporary society is increasing. In Brazil, 51.4% of the waste produced is organic. Composting is a possibility of treatment of these residues, which consists of the spontaneous biological decomposition of organic matter. The goal of this study was to reduce the time of maturation of the compost in the composting process, to test the compounds produced and to size two composting yards (conventional and potentiated). Four compost piles (1: control, 2: aeration facilitated, 3: aeration and chemical fertilizer, and 4: chemical fertilizer) were built for 400 kg of industrial organic waste and 400 kg of urban organic waste. The parameters followed were: pH, temperature, humidity and C / N ratio. Piles 1 and 2 stabilized with 58 days for industrial waste and 56 days for urban waste. Piles 3 and 4 stabilized with 35 days for both residues. Compounds produced from the industrial residues were applied in the culture of lettuces under natural conditions with 4 treatments (1: control, 2: commercial compound, 3: composed of piles 1 and 2, 4: composed of piles 3 and 4). A second application of the compounds under natural and greenhouse conditions was carried out by adding the treatments 5 and 6 with compounds produced from the urban waste (5: composed of piles 1 and 2, 6: composed of piles 3 and 4). The results obtained in the treatments were submitted to the ANOVA statistical test. It was observed with 95% confidence that treatments 4 and 6 (fertilizer compounds) were the most effective in plant growth. Finally, two composting yards were designed for a medium-sized municipality, a conventional one with a stabilization time of 90 days that would have to have 6.58 ha, and one with a stabilization time of 35 days with 1.69 ha. It is concluded that pile 3 is more efficient because it has a shorter stabilization time, does not require manual stirring and produces a compound with higher nutrient content. The potted composting yard needs a 74.32% smaller area than the conventional one, thus enabling the application of composting for the treatment of organic waste.